Thermodynamics of the glassy state - Leuzzi, Luca.; Nieuwenhuizen, Theo M. (New York : London : Taylor & Francis, 2008)
What does being a manager mean to those who do managerial work and why has becoming a manager become so attractive for so many people? How does pursuing a managerial career fit with the wider project of constructing a life and a sense of self? This illuminating and thoughtful book answers these questions by considering the extended life histories of ten managers, allowing their own voices to be heard. The Manager's Tale uses the ideas of Heidegger, Sartre and Ricoeur to show that who a person is can be seen as a narrative accomplishment, a result of the stories we tell ourselves and others. Within this framework the manager's stories are revealed, highlighting the complex ways in which dominant expectations of what it means to be a successful individual in the modern world influences what sort of person we strive to be.
Includes bibliographical references and index.
Keywords: Spin glasses; Glass